Discovery and characterization of the feline miRNAome - Alessandro Laganà; Wessel P. Dirksen; Wachiraphan Supsavhad; Ayse Selen Yilmaz; Hatice G. Ozer; James D. Feller; Kiersten A. Vala; Carlo M. Croce; Thomas J. Rosol (Scientific Reports, 2017)
Abstract The domestic cat is an important human companion animal that can also serve as a relevant model for ~250 genetic diseases, many metabolic and degenerative conditions, and forms of cancer that are analogous to human disorders. MicroRNAs (miRNAs) play a crucial role in many biological processes and their dysregulation has a significant impact on important cellular pathways and is linked to a variety of diseases. While many species already have a well-defined and characterized miRNAome, miRNAs have not been carefully studied in cats. As a result, there are no feline miRNAs present in the reference miRNA databases, diminishing the usefulness of medical research on spontaneous disease in cats for applicability to both feline and human disease. This study was undertaken to define and characterize the cat miRNAome in normal feline tissues. High-throughput sequencing was performed on 12 different normal cat tissues. 271 candidate feline miRNA precursors, encoding a total of 475 mature sequences, were identified, including several novel cat-specific miRNAs. Several analyses were performed to characterize the discovered miRNAs, including tissue distribution of the precursors and mature sequences, genomic distribution of miRNA genes and identification of clusters, and isomiR characterization. Many of the miRNAs were regulated in a tissue/organ-specific manner.